Mary is a Model of Faith and Moral Life for the Contemporary Disciples of Christ - Marek Kluz (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Observing the transformations taking place in the world, it is important to note the need for continuous reference in various areas of human life to Mary, whose example is always relevant. Therefore, the purpose of this article is to present Mary as a model of faith and moral life for the contemporary disciples of Christ. Mary – with her example – teaches one how to be a disciple of Christ in an authentic way, not superficial one. She is an example of understanding the Christian life as a commitment. Looking to Mary as an example, the individual learns to obey God in the path of faith and finds the values that lead him or her through the paths of the Christian moral life. Life permeated with the Marian spirit becomes an inspiration for the contemporary disciples of Christ to grow in faith, to do good and radically reject everything which is in contrary to the Christian ideal.